Recent Advances in Natural Polysaccharide-Based Hemostatic Sponges: A Review - Yingying Guo; Xuan Xie; Jing Li; Shun Yao (Polysaccharides, 2025)
Bleeding is a potentially life-threatening emergency that can result in severe complications or death regardless of the cause of bleeding. The development of hemostatic materials has been a long-standing concern for emergency treatment in surgery and combat. In recent years, there have been many reviews on hemostatic materials, but there have been few specific studies about performance requirements and development in recent years on natural polysaccharide-based hemostatic sponge as a type of hemostatic excipient. Currently, natural polysaccharide hemostatic sponge has attracted wide attention due to the enhancement or interaction of various hemostatic mechanisms. These polysaccharide sponges show a high hemostatic effect. In this paper, the application history of natural polysaccharides (chitosan, hyaluronic acid, alginate, cellulose, starch, etc.) as a new generation of hemostatic sponge materials in recent years is reviewed. The design principles and new achievements in polysaccharide-based hemostatic sponge are introduced. Finally, we summarize the advantages and disadvantages of polysaccharide hemostatic sponge and prospect the development opportunities and challenges of this material.